Code-Switching Patterns Among Indonesian Digital Native Youth: A Sociolinguistic Analysis of Computer-Mediated Communication - Muhammad Ali Imran; Nurasia Natsir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Code-switching has become increasingly prevalent in digital communication among Indonesian youth, reflecting complex sociolinguistic dynamics in multilingual contexts. This study investigates code-switching patterns in Indonesian digital native youth's computer-mediated communication (CMC), examining the linguistic structures, social functions, and motivations behind this phenomenon. A mixed-methods approach was employed, analyzing 2,500 social media posts from 150 Indonesian youth aged 18–25 across Instagram, Twitter, and WhatsApp. Quantitative content analysis identified code-switching frequency and patterns, while qualitative thematic analysis explored motivations and functions. Myers-Scotton's Matrix Language Frame model guided the structural analysis. Results revealed that 78.4% of participants engaged in code-switching, with Indonesian-English being the most common pattern (62.3%), followed by Indonesian-Regional Language (23.5%) and trilingual switching (14.2%). Intrasentential switching occurred in 54.7% of cases, while intersentential switching appeared in 31.8%. Five primary functions emerged: identity construction (32.1%), emphasis/intensification (26.4%), topic shifting (18.9%), humor/creativity (14.3%), and lexical gap-filling (8.3%). Code-switching in Indonesian digital communication represents a sophisticated linguistic practice driven by identity negotiation, expressive needs, and technological affordances rather than linguistic deficiency. These findings contribute to understanding multilingual CMC in Southeast Asian contexts and have implications for digital literacy education and language policy.